An overview of the characteristics of women with breast cancer at Haji Hospital Medan - Tri Suci Dewi Wati; Ayu Dwi Fani Br. sitepu (Institute of Computer Science (IOCS), 2019)
Breast cancer is the uncontrolled growth of breast cells due to abnormal changes in the genes responsible for regulating cell changes. In Indonesia the incidence rate is 4.3 out of 100 000 population and cancer is the 7th highest cause of death after tuberculosis, hypertension, injury, perinatal, and diabetes mellitus. 2011-2012. Research methodology: The research is descriptive, by obtaining secondary data from the medical records of Medan Haji Hospital, with a total sample of 70 cases. Data collection began in May 2013 using a checklist sheet containing sociodemographic data, clinical stages, and medical measures. Results: From the data analysis, it can be seen that in the age group > 40 years people are 76.9%, high school education level is (51.3%), work as a housewife (44.9%), marital status (100%) is married, stage IV as much as (29.5%). Surgery + chemotherapy (33.3%) and length of stay < 12 days (100%). Conclusion: age < 40, high school education, work as a housewife, most clinical stage Stage IV, medical action and length of stay are the most characteristic or variable in mothers who experience breasts at Haji Hospital Medan, Suggestions: